Modern Agriculture Development Case in Gobleg Village Banjar Subdistrict Buleleng Regency, Bali Province - Sudiarsana, I Gede Artha; Ustriyana, I Nyoman Gede; Putra, I Gede Setiawan Adi (JURNAL MANAJEMEN AGRIBISNIS; Vol 12 No 1 (2024): Jurnal Manajemen Agribisnis, 2024)
The challenges of Indonesia's agricultural development today are climate change and potential droughts. This research aims to analyze the modern agricultural development of the Gobleg Village Case of Banjar district of Buleleng. This research uses a qualitative method with a case study approach. Determination of informants using snowball sampling and data collection methods is done with in-depth interviews, observations, and documentation. Data analysis using interactive model analysis of Miles, Huberman and Saldana (2014). The results of the research show the selection of commodities based on potential income, level of market demand, knowledge, land characteristics and socio-cultural characteristics. The agricultural production process ranges from land processing to post-harvest harvesting. Farmers have already implemented eco-friendly farming by implementing IoT-based fertigation. Institutional support consists of marketing, financing, technical guidance and social capital. The marketing of products is facilitated by the Gobleg PMK cooperation in cooperation with Bali Organic Subak, the marketing is done online with the Fresh Boss application. The cooperation provides facilitation of means of production with the payment system after harvest. In terms of social capital, farmers still exist doing gotong royong in land processing. Farmers are already able to leverage technology like smartphones that are integrated with IoT-based fertigation.